Policy on Responsible Use of Information Technology Resources
Purpose:The purpose of this policy is the effective and efficient use of information technology resources in support of the University's mission of education, research, and public service. This policy is intended to ensure 1. The integrity, reliability, and good performance of University resources; 2. That these resources are used appropriately and efficiently for their intended purposes; and 3. That appropriate measures are in place to assure the policy is enforced.